Real-Time Visualization of Embryonic Apoptosis Using a Near-Infrared Fluorogenic Probe for Embryo Development Evaluation - He, Lei; Ye, Shuyue; Fang, Jing; Zhang, Yuqi; Cui, Chaoxiang; Wang, Anna; Zhao, Yan; Shi, Haibin (Analytical chemistry (Washington), 2021)
Developing an accurate and reliable detection technique for early embryonic apoptosis is of great significance for real-time monitoring and evaluation of embryonic development in living systems. Herein, we have rationally designed and synthesized a novel near-infrared (NIR) fluorogenic probe CGK(QSY21)DEVD-Cy5.5 for real-time imaging of embryonic apoptosis. This probe is constructed with a NIR dye Cy5.5, a fluorescence quencher QSY21, and a peptide substrate Asp-Glu-Val-Asp (DEVD) of the caspase-3 enzyme that is a key executor of cell apoptosis. The probe was initially nonfluorescent in aqueous solution but emitted strong NIR fluorescence upon specific cleavage by activated caspase-3 in a concentration-dependent manner. Taking advantage of this unique feature, this fluorogenic probe was for the first time used for real-time imaging of caspase-3 activity in apoptotic embryos. More notably, significant fluorescence enhancement was solely determined from the apoptotic embryos with the treatment of the probe both in vitro and in vivo, highly suggesting that this probe has great potential to monitor the apoptosis of embryos. We thus envision that this probe would provide a very useful means for real-time visualization and accurate evaluation of embryonic development in the future.